(untitled) (Global Journal of Science Frontier Research, 2023)
Climate change is projected to produce a lesser amount of expectable rainfall patterns coupled with extensive droughts intermixed with fleeting but torrential rainfall which has implications on food security risks The paper examines the role of Non-State Actors NSAs specifically Non-Governmental Organizations NGOs in climate change governance and how they address food security risks thereof The study addresses this objective by placing a special emphasis on the modus operandi of NGOs in helping smallholder farmers navigate through their farming cycle successfully in the Northern belt of Ghana The study adopts the content analysis and critical stage review of extant literature and other datasets The study observes that NGOs help smallholder farmers to build their resilience against the ravages of climate change using a more comprehensive approach along the entire value chain of the farming cycle before during and after the crop planting exercises Consequently we develop and discuss the NSAs-holistic empowerment framework which will contribute to policy practice and literature on the topic The study contends that the impact of most NSAs in climate change is contingent on the resources available and their organizational prowess The study argues for the need to forge a synergistic relationship and networks between the public and non-state actors to effectively play a more nuanced role in climate change efforts at all levels which will help address food insecurity in areas and regions currently experiencing drought hunger and under nutrition